Systemic Immune-Inflammation Index Predicts Contrast-Induced Acute Kidney Injury in Patients Undergoing Coronary Angiography: A Cross-Sectional Study - Jiang, Hangpan; Li, Duanbin; Xu, Tian; Chen, Zhezhe; Shan, Yu; Zhao, Liding; Fu, Guosheng; Luan, Yi; Xia, Shudong; Zhang, Wenbin (Frontiers in Medicine, 2022)
Abstract Background and aims: Systemic immune-inflammation index (SII) is an emerging indicator and correlated to the incidence of cardiovascular diseases. This study aimed to explore the association between SII and contrast-induced acute kidney injury (CI-AKI). Methods: In this retrospective cross-sectional study, 4381 subjects undergoing coronary angiography (CAG) were included. SII is defined as neutrophil count×platelet count/lymphocyte count. CI-AKI was determined by the elevation of serum creatinine (Scr). Multivariable linear and logistic regression analysis were used to determine the relationship of SII with Scr and CI-AKI, respectively. Receiver operator characteristic (ROC) analysis, structural equation model analysis, and subgroup analysis were also performed. Results: Overall, 786 (17.9%) patients suffered CI-AKI after the intravascular contrast administration. The subjects were 67.1±10.8 years old, with a mean SII of 5.72×1011/L. Multivariable linear regression analysis showed that SII linearly increased with the proportion of Scr elevation (β [95% confidence interval, CI]=0.315 [0.206 to 0.424], P <0.001). Multivariable logistic regression analysis demonstrated that higher SII was associated with an increased incidence of CI-AKI ([≥12 vs. <3×1011/L]: odds ratio, OR [95%CI]=2.914 [2.121 to 4.003], P <0.001). Subgroup analysis showed consistent results. ROC analysis identified a good predictive value of SII on CI-AKI (area under the ROC curve [95%CI]: 0.625 [0.602 to 0.647]). The structural equation model verified a more remarkable direct effect of SII (β=0.102, P <0.001) on CI-AKI compared to C-reactive protein (β=0.070, P <0.001). Conclusions: SII is an independent predictor for CI-AKI in patients undergoing CAG procedures.